ANALISIS LITERATUR: INTERAKSI ANTARA JOB DEMAND, KOMPETENSI SDM, DAN PROFESIONALISME DALAM LINGKUNGAN KERJA MODERN - Husniati, Renny; Rahmi, Mira (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The transformation of the modern work environment in Indonesia over the past two years, marked by accelerated digitalization, structural organizational changes, and increasingly fierce global competition, has given rise to new challenges related to increased job demands on human resources (HR). This article aims to analyze the interaction between job demand, HR competencies (both hard skills and soft skills), and professionalism in shaping adaptive and highly competitive organizational performance. Through a review of literature and the latest national data, this article finds that the development of HR competencies relevant to the needs of the digital age, supported by strong integrity and professional ethics, serves as the primary foundation for managing work pressure and driving innovation within the organizational environment. Optimal synergy between these three aspects not only enhances productivity and the quality of work output but also strengthens mental resilience and individual commitment in facing dynamic organizational stressors. The implications of this analysis underscore the importance of HR policies focused on people-centric development, continuous training, and balanced work management between demands and empowerment, to ensure organizational sustainability and excellence in the era of global competition and national digitalization.